Prohibitin, STAT3 and SH2D4A physically and functionally interact in tumor cell mitochondria - Plöger, Carolin; Huth, Thorben; Sugiyanto, Raisatun Nisa; Pusch, Stefan; Goeppert, Benjamin; Singer, Stephan; Tabti, Redouane; Haußer-Siller, Ingrid; Schirmacher, Peter; Désaubry, Laurent; Rössler, Stephanie (Cell death & disease, 2020)
Chromosome 8p is frequently deleted in various cancer entities and has been shown to correlate with poor patient survival. SH2D4A is located on chromosome 8p and prevents the nuclear translocation of the pro-tumorigenic transcription factor STAT3. Here, we investigated the interaction of SH2D4A and STAT3 to shed light on the non-canonical functions of STAT3 in cooperation with the tumor suppressor SH2D4A. Using an immunoprecipitation-mass spectrometry (IP-MS) approach, we identified the mitochondrial scaffold proteins prohibitin 1 (PHB1) and prohibitin 2 (PHB2) among other proteins to potentially bind to SH2D4A. Co-immunoprecipitation and proximity ligation assays confirmed direct interactions of STAT3, PHB1, and SH2D4A in situ and in vitro. In addition, cell fractionation and immunofluorescence staining revealed co-localization of these proteins with mitochondria. These interactions were selectively interrupted by the small molecule and PHB ligand FL3. Furthermore, FL3 led to a reduction of STAT3 protein levels, STAT3 transcriptional activity, and HIF1α protein stabilization upon dimethyloxalylglycine (DMOG) treatment. Besides, mitochondrial fusion and fission markers, L-OPA1, Mfn1, and FIS1, were dysregulated upon FL3 treatment. This dysregulated morphology was accompanied by significant reduction of mitochondrial respiration, thus, FL3 significantly diminished mitochondrial respirational capacity. In contrast, SH2D4A knockout increased mitochondrial respiration, whereas FL3 reversed the effect of SH2D4A knockout. The here described results indicate that the interaction of SH2D4A and PHB1 is involved in the mitochondrial function and integrity. The demonstrated interaction with STAT3, accompanied by its reduction of transcriptional activity, further suggests that SH2D4A is linking STAT3 to its mitochondrial functions, and inhibition of PHB-interaction may have therapeutic effects in tumor cells with STAT3 activation.
Gesehen am 26.01.2021